PENGARUH PENERAPAN STRATEGI DOMINO GAME TERHADAP PEMAHAMAN KONSEP MATEMATIS SIWA KELAS VIII SMPN 11 PADANG - Ratnasari, Dewi; Aima, Zulfitri; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTÂ The background of this research is student assume study of mathematics is difficult and boring and then comptehend of mathematics concepts of students is very low. The aims of this research is to know the studentsâ understanding of mathematical concept by applying Strategy Domino Game to understanding mathematical concept class student of VIII SMPN 11 Padang. The kind of this research is experimental research by random design towards the subject. The population in this research was students in VIII grade SMPN 11 Padang in school year 2013/2014. The sample Class choses VIII.C class as experimental class and VIII.B class as control class. The instrument which was used is final test. form of Tes the used is essay and obtained by problem which is reliabel. Technique of data analysis using t-test of the side with MINITAB software. Based the of hypothesis test obtained by P-Value 0,037 less than that is 0,05, hence research hypothesis accepted. Inferential that understanding of mathematical concept of student by using strategy Domino Game better than the understanding of mathematical concept of student use conventional study.